Global Research Trends on Deferred Tax: A Comprehensive Bibliometric Analysis Using Scopus Data (2016–2025) - Markhumah, Umatun; Sutopo, Bambang (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study presents a comprehensive bibliometric analysis of the Scopus-indexed deferred tax literature, focusing on conceptual evolution, thematic interrelationships, and global research directions over the past two decades. Using VOSviewer for co-occurrence mapping, five main clusters are identified that reflect the knowledge structure on deferred taxes. The first cluster positions deferred tax, deferred tax asset, and deferred tax liability as core concepts closely related to IAS 12, temporary differences, and DTA/DTL recognition practices. The second cluster highlights the relationship between earnings management, value relevance, and book tax differences, confirming that deferred tax is an important indicator of earnings quality. The third cluster highlights the role of tax loss carryforwards in risk assessment, financial performance, and information relevance for investors. The fourth cluster links tax avoidance, effective tax rate, and transfer pricing, suggesting that DTA/DTL are used as signals of tax aggressiveness and are influenced by governance mechanisms. The fifth cluster focuses on valuation allowances and cash flow uncertainty, underscoring the importance of tax accounting in assessing reporting risk. These findings suggest that the deferred tax literature has shifted from a technical focus on accounting recognition to broader issues, including cash flow forecasting, firm risk, governance, tax aggressiveness, and ESG implications emerging after 2020. This study provides a strong theoretical foundation for further research, including exploring the integration of deferred taxes with sustainability, tax transparency, and financial reporting innovation under the latest IFRS standards. These results also contribute to academics, regulators, and practitioners in understanding the strategic position of deferred taxes in corporate financial decision-making.